Functional characterization of spectral tuning mechanisms in the great bowerbird short-wavelength sensitive visual pigment (SWS1), and the origins of UV/violet vision in passerines and parrots - van Hazel, Ilke (BioMed Central, 2013)
BACKGROUND: One of the most striking features of avian vision is the variation in spectral sensitivity of the short wavelength sensitive (SWS1) opsins, which can be divided into two sub-types: violet- and UV- sensitive (VS & UVS). In birds, UVS has been found in both passerines and parrots, groups that were recently shown to be sister orders. While all parrots are thought to be UVS, recent evidence suggests some passerine lineages may also be VS. The great bowerbird (Chlamydera nuchalis) is a passerine notable for its courtship behaviours in which males build and decorate elaborate bower structures. RESULTS: The great bowerbird SWS1 sequence possesses an unusual residue combination at known spectral tuning sites that has not been previously investigated in mutagenesis experiments. In this study, the SWS1 opsin of C. nuchalis was expressed along with a series of spectral tuning mutants and ancestral passerine SWS1 pigments, allowing us to investigate spectral tuning mechanisms and explore the evolution of UV/violet sensitivity in early passerines and parrots. The expressed C. nuchalis SWS1 opsin was found to be a VS pigment, with a λ(max) of 403 nm. Bowerbird SWS1 mutants C86F, S90C, and C86S/S90C all shifted λ(max) into the UV, whereas C86S had no effect. Experimentally recreated ancestral passerine and parrot/passerine SWS1 pigments were both found to be VS, indicating that UV sensitivity evolved independently in passerines and parrots from a VS ancestor. CONCLUSIONS: Our mutagenesis studies indicate that spectral tuning in C. nuchalis is mediated by mechanisms similar to those of other birds. Interestingly, our ancestral sequence reconstructions of SWS1 in landbird evolution suggest multiple transitions from VS to UVS, but no instances of the reverse. Our results not only provide a more precise prediction of where these spectral sensitivity shifts occurred, but also confirm the hypothesis that birds are an unusual exception among vertebrates where some descendants re-evolved UVS from a violet type ancestor. The re-evolution of UVS from a VS type pigment has not previously been predicted elsewhere in the vertebrate phylogeny.